Combined therapy of experimental pancreatic cancer with CYP2B1 producing cells: Low-dose ifosfamide and local tumor irradiation - Ryschich, Eduard; Jesenofsky, Ralf; Ringel, Jörg; Harms, Walter; Fabian, Oliver V.; Saller, Robert; Schrewe, Michael; Engel, Alexander; Schmidt, Jan; Löhr, J.-Matthias (International journal of cancer, 2005)
Local therapy of pancreatic cancer with microencapsulated CYP2B1-producing cells and ifosfamide showed an effect both on the primary tumor and on distant metastatases. This possibly represents a consequence of the activation of immune response. Other studies have demonstrated that local tumor irradiation leads to the activation of the intratumoral lymphocyte infiltration. The aim of our study was to investigate the efficacy of the combined therapy with low-dose irradiation, ifosfamide and CYP2B1-producing cells. Syngenic pancreatic cancer was induced in 38 Lewis-rats by subcutaneous inoculation of 1 × 106 (DSL6A) tumor cells. Microencapsulated CYP2B1-producing cells were injected peritumorally 10--12 weeks after tumor implantation. Animals were randomized to the following groups: 1) control (NaCl, 1 ml i.p.), 2) ifosfamide (50 mg/kg, i.p., (3×/week), 3) local irradiation with 5 Gy and 4) ifosfamide plus irradiation. The tumor growth was monitored for 3 weeks. The tumor infiltration with CD4+, CD8+, NK-cells, microvessel density and proliferation rates were investigated by immunohistochemistry. Cytokine plasma level for TNF-α were measured by ELISA. Seven of 9 animals in the group of combined therapy showed an objective response to the therapy. The therapy with ifosfamide or radiation alone showed 5 and 3 responders, respectively. The mean tumor volume was significantly reduced after combined ifosfamide plus radiation therapy in the first week, whereas monotherapy with ifosfamide or radiation significantly decreased tumor growth earliest after 2 and 3 weeks, respectively. The high plasma level of TNF-α in the control group was significantly reduced after combined ifosfamide/irradiation treatment. The lymphocyte infiltration and tumor proliferation were not significantly different between the groups. Microvascular density was significantly increased after ifosfamide and ifosfamide plus irradiation therapy. The combination of ifosfamide/CYP2B1-producing cells and irradiation showed an earlier therapeutical effect on the growth of rat pancreatic cancer than the irradiation or ifosfamide alone. There was no evidence of late activation of lymphocyte infiltration and PCNA-positive tumor cells.
First published: 30 November 2004
Gesehen am 23.05.2022